Bilgisayar destekli ortopedik ayakkabı kalıp tasarımı ve imalatı - Yorulmaz, Aynur (My University, 2006)
Tezin ana temasını “Bilgisayar Destekli Ortopedik Ayakkabı Taban Tasarımı ve İmalatı” başlığı teşkil etmektedir. Tezimizde ayakkabı hakkında bilgiler vermeye çalıştık. Ayakkabının genel tanımını yaparak ayakkabının sınıflandırılması, ayakkabıda kullanılan malzemeleri, numaralandırma sistemlerini ifade ettik. Ayakkabıcılıkta ülke bazında hangi konumda olduğumuzu ve Avrupa’ya göre yerimizi, İstanbul Sanayi Odası’ndan aldığımız bilgilere istinaden tezimize ilave ettik. Ayrıca eğitimin ülkemizde ne durumda olduğunu, TASEV’in faaliyetlerini, eğitimin sorunlarını I.Bölümde ifade ettik. IV. Bölüm’de ise tamamen uygulamaya geçerek sanayide bu işler nasıl yapılıyor, en yeni teknolojiler alt taban yapımına nasıl tatbik ediliyor, ortopedik bir iç tabanın imalat aşamaları nelerdir, gibi sorulara yanıt vermeye çalıştık.

The main theme of the thesis is “Computer Aided Sport Orthopedic Shoe Sole Design and Manufacturing”. In our thesis we tried to give detailed information about shoes. First we made the general naming of the “shoe” and then we classified them. Then we explained the substances for making shoe and we explained the numbering systems. We included the detailed information that we got from ISO, about our country’s shoe making situation among other countries and our place among European countries especially. Also we included the information that we got from TASEV, about the shoe making education and the problems in our country. We named these information as the first section. In the fourth section we totally concentrated on the application and tried to answer the questions as “how do these works accomplished in the industry?”, “how do the newest technologies are applied to the sole design?” and “What are the production steps of the orthopedic inner sole design?”
Keywords: Ayakkabı_Üretim_Tasarım